2013
DOI: 10.1021/nn400659m
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Spatial Distribution of Thiolated DNA on Model Nucleic Acid Sensor Surfaces

Abstract: The nanoscale arrangement of the DNA probe molecules on sensor surfaces has a profound impact on molecular recognition and signaling reactions on DNA biosensors and microarrays. Using electrochemical atomic force microscopy, we have directly determined the nanoscale spatial distribution of thiolated DNA that are attached to gold via different methods. We discovered significant heterogeneity in the probe density and limited stability for DNA monolayers prepared by the backfilling method, that is, first exposing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
94
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(95 citation statements)
references
References 52 publications
1
94
0
Order By: Relevance
“…the electrode was immersed first in MCH, then in DNA), much more homogeneous layers were obtained. [20] Interestingly, these results were recently confirmed at the molecular level by Ye and Josephs, [27] who performed high-resolution atomic force microscopy experiments and reached similar conclusions regarding the influence of the preparation procedure on the spatial homogeneity of DNA SAMs.…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…the electrode was immersed first in MCH, then in DNA), much more homogeneous layers were obtained. [20] Interestingly, these results were recently confirmed at the molecular level by Ye and Josephs, [27] who performed high-resolution atomic force microscopy experiments and reached similar conclusions regarding the influence of the preparation procedure on the spatial homogeneity of DNA SAMs.…”
Section: Introductionsupporting
confidence: 58%
“…Murphy et al [20] and Josephs and Ye [27] showed that this procedure produces very inhomogeneous surfaces, whereas with the use of the reversed procedure (diluent immobilized first and backfilling with DNA, procedure P3) DNA is adsorbed in the defect sites of the initial SAM of MCH, which provides a less heterogeneous but more diluted mixed SAM. In this work, we tested a third procedure, in which DNA and MCB were co-adsorbed together in a single step (procedure P1).…”
Section: Investigation Of the Heterogeneity Of The Samsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunofluorescence staining procedures mainly refer to the documented protocol with minor modifications (Josephs et al, 2013;Ko et al, 2005;Schmidt et al, 1980;Wan et al, 2014). As follows: The cells were fixed with 4% paraformaldehyde for 30 min at room temperature and washed with ice pre-cold PBS, permeabilized with 0.5% Triton X-100 in PBS for 20 min (room temperature), blocked with 0.5% BSA/PBS for 1 h and then incubated with fluorescent antibody (1:10) overnight in the dark at 4°C.…”
Section: Immunofluorescence Stainingmentioning
confidence: 99%
“…As shown in Scheme 1, in the cytosensor, we inserted the capture probe in the 6-mercapto-1-hexanol (MCH) interspaces after MCH immobilized for the capture probe standing and more uniformly distributing onto the gold electrode surface (Josephs et al, 2013). The strategy could contribute to hybridize with aptamer and capture more CTCs, and then improved the sensitivity.…”
Section: Introductionmentioning
confidence: 99%